The Annual Report, Indicator of Library Transparency. Issue 4 (1st December 2020) - Pacios, Ana R.; Serna, Ignacio
Abstract: This article addresses the annual reports published by Spanish university libraries on their websites. Report form and content were analyzed, along with availability, timing and position on the library's website with the concomitant visibility and accessibility. Although some of the items included (collection, services, staff, premises and facilities) were found to be the same year after year, the degree of detail furnished was observed to vary. New subjects were also identified: partnering, cooperation, communication, marketing, dissemination, presence in social networks and libraries' impact on their surrounds. Annual reports and their dissemination among stakeholders are recommended as an exercise in accountability and management transparency.